Large herbivore assemblages in a changing climate: Incorporating water dependence and thermoregulation - Veldhuis,M. P; Kihwele, E. S; Cromsigt, J. P; Ogutu,G. M; Hopcraft, J. O; Smith, J. G. C.; Owen, N.; Olff, H. (Ecology Letters published by CNRS and John Wiley & Sons Ltd., 2024)
Research article submitted to ecology letters of 2019